HBV markers and antibody protective level among Iraqi vaccinated and unvaccinated subjectes - AL-Shammary, Adel; Al-Diwan, Jawad K.; AL-Ani, Nafi; AL-Hadithi, Tariq S.; Omer, ALI. R. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Iraq is among counttries of intermediate hepatitis B endemicity. Although several studies have been carried out on the prevalence of HBV markers.